PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PERJUDIAN ONLINE HIGGS DOMINO ISLAND OLEH KEPOLISIAN SEKTOR BUKIT KAPUR KOTA DUMAI - Warni Susila; Davit Rahmadan; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Gambling is regulated in Article 303 paragraph (1) the Criminal Codewith threats for preparatos namely imprisonment for a maximum of 10 (ten) yearsand a maximum fine of Rp. 25,000.000,00 (twenty-five million rupiah). However,in reality enforcement regarding gambling is still not optimal, this can be seenfrom the large number of people who freely acces or play online gambling,especially higgs domino island which occured in Bukit Kapur, Dumai City. Thisaims to: first, to determine law enforcement against erpetrators of criminal acts ofonline gambling on higgs domino island by the Bukit Kapur sector police. Second,tooutline the obstacles in law enforcement against criminal acts of higgs dominoisland gambling in the jurisdiction of the Bukit Kapur Sector Police. Third, tooutline the efforts made by the police to overcome obstacles in enforcing criminalacts of higgs domino island online gambling.This type of research can be classified as sociological legal research,because in this research it is carried out by looking at the effect of the enactmentof posisitive law on people’s lives. This research was conducted at the BukitKapur Police, Dumai City. In this studet, the data sources used were primary dataand secondary data. Data collection techniques in this study were interviewes andliterature review.From the results of the research conductes, it can be concluded that lawenforcement carried out by the Bukit Kapur Sector Police in the City of Dumaihas not been fully effective, this is influenced by several factors, namely the legalfactors themselves, law enforcers, facilities and infrstrusture, comunity dancultural factors. Obstacles in enforcing the higgs domino island online gamblinglaw faced by the Bukit Kapur Police include factors, law enforcers, faciltaties andinfrastructure and the community. The efforts made by the police are conductingoutreach, cooperating with the community, taking strict action against onlinegambling actors.Keywords: Law Enforcment – Crime – Online Gambling